Validitas Modul Proyek â€œLegenda Surabayaâ€ Berbantukan Qr Code Kurikulum Merdeka Fase B - Ahmad Mahmudi; Setya Yuwana; Titik Indarti; Hendratno Hendratno (Universitas Muhammadiyah Surabaya, 2023)
Validity of